2016
DOI: 10.1080/08897077.2015.1132292
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Recommendation of 12-Step Meeting Attendance and Discussion regarding Disclosure of Buprenorphine use among Patients in Office-Based Opioid Treatment

Abstract: Clinicians recommended 12-step meetings to most patients but did not routinely discuss issues of disclosure. Despite utilizing 12-step meetings and reporting them to be helpful, many avoided disclosing their use of buprenorphine to others. More research is needed to better understand how clinicians may assist patients to best utilize 12-step meetings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Hierarchies can function as an impediment to peer support and deter women from treatment engagement. Considering the range of hierarchies [ 48 , 49 ] that may be present between women in clinical- and community-based treatment settings may offer important direction for future iterations of women-specific MOUD treatment programming. To be trauma-informed [ 50 ], women-specific treatment programs should address relational factors that impact women [ 51 , 52 , 53 ], and incorporate guidelines for skill-building to improve communication so these groups can be sources of positive social support.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchies can function as an impediment to peer support and deter women from treatment engagement. Considering the range of hierarchies [ 48 , 49 ] that may be present between women in clinical- and community-based treatment settings may offer important direction for future iterations of women-specific MOUD treatment programming. To be trauma-informed [ 50 ], women-specific treatment programs should address relational factors that impact women [ 51 , 52 , 53 ], and incorporate guidelines for skill-building to improve communication so these groups can be sources of positive social support.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In the current results, some prescribers had concerns about whether 12-step meetings in their community were accepting of patients receiving buprenorphine treatment, a concern that has also been raised by patients. 24 In addition, it is important to note that buprenorphine prescribers are required to be able to refer patients to PIs, but referrals are not mandatory. 4 The contrast we see between limited evidence on PIs to date and the importance prescribers place on PIs and their utilization may reflect the need by prescribers to address comorbid psychiatric and other substance use disorders, which are highly prevalent in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these nuances is important for treatment professionals. A survey of patients receiving bup-nx found that a considerable percentage (30%) were worried about encountering negative attitudes toward their buprenorphine use; only 33% of participants reported that their providers had discussed disclosing their buprenorphine use 27 . Monico and colleagues 23 found that NA members receiving buprenorphine used various strategies to deal with this issue, including limiting disclosure of their buprenorphine prescriptions and avoiding particular meetings.…”
Section: Many Patients Have Encountered the Traditional View Held By mentioning
confidence: 99%